Autoimmune hepatitis as a rare cause of cirrhosis development - Dominika Podgórska; Karolina Jurasz; Miłosz Sanecki; Karolina Tomczyk; Natalia Chojnacka; Ewa Rzeska; Jakub Klarycki; Radosław Cymer (Kazimierz Wielki University, 2024)
Cirrhosis is a serious condition associated with progressive damage to this organ. Autoimmune hepatitis (AIH) is one of the causes leading to the development of cirrhosis. This disease is characterized by chronic inflammation with damage to hepatocytes and presence of specific immune markers. The diagnosis of AIH is based on biochemical, immunoserological and histopathological tests. There are defined diagnostic criteria, liver biopsy is important in determining the extent of the disease. Symptoms of AIH are nonspecific and include weight loss, fatigue, jaundice, abdominal pain and symptoms associated with the overactivity of an immune system. Advanced cases of AIH can lead to cirrhosis. AIH most often affects middle-aged women, although it can occur in people of any age. Epidemiological data indicate an increase in the incidence of AIH, which may be related to various environmental factors. The rate of progression of AIH to cirrhosis and depends on a number of factors. Effective treatment includes immunosuppression, mainly the use of glucocorticosteroids and azathioprine. Monitoring, healthy lifestyle and patient education are key. In severe cases, liver transplantation may be necessary.